2022
DOI: 10.3389/fcell.2022.812728
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in the Neuronal Ceroid Lipofuscinoses (Batten Disease)

Abstract: The neuronal ceroid lipofuscinoses (NCLs), also referred to as Batten disease, are a family of neurodegenerative diseases that affect all age groups and ethnicities around the globe. At least a dozen NCL subtypes have been identified that are each linked to a mutation in a distinct ceroid lipofuscinosis neuronal (CLN) gene. Mutations in CLN genes cause the accumulation of autofluorescent lipoprotein aggregates, called ceroid lipofuscin, in neurons and other cell types outside the central nervous system. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 321 publications
(600 reference statements)
0
7
0
Order By: Relevance
“…(ii) Autophagy. Dysregulation of autophagy has been suggested as a common mechanism in the pathogenesis of NCLs ( 54 ). We found that KCTD7-deficient cells display autophagic defects and are sensitive to nutrient deprivation–induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) Autophagy. Dysregulation of autophagy has been suggested as a common mechanism in the pathogenesis of NCLs ( 54 ). We found that KCTD7-deficient cells display autophagic defects and are sensitive to nutrient deprivation–induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case with CLN3 disease. Research in various model organisms has highlighted the importance of CLN3 protein function in autophagy, indicating that it influences the expression and activity of lysosomal enzymes and modulates vesicular trafficking and autophagic degradation ( 23 ). It is not known whether Trehalose administration may also have a benefit on cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq identified DEGs in cln5 - cells associated with protein tagging, protein degradation, and autophagy, which aligns with studies from D. discoideum , mice, and humans linking the function of CLN5 to autophagy ( Best et al, 2017 ; Leinonen et al, 2017 ; Huber and Mathavarajah, 2018b ; Adams et al, 2019 ; Doccini et al, 2020 ; Basak et al, 2021b ; McLaren et al, 2021 ). Intriguingly, autophagy is dysregulated in many NCL subtypes ( Kim et al, 2022 ). Accumulated evidence suggests that autophagy and the ubiquitin-proteasome system work together to regulate protein degradation and operate in a compensatory manner when one of the pathways is inhibited ( Kocaturk and Gozuacik, 2018 ).…”
Section: Discussionmentioning
confidence: 99%